(untitled) (World Bulletin of Management and Law, 2024)
This article discusses the issues of international legal regulation of intellectual property. The international normative legal acts in the field of intellectual property are analyzed. The activity of international bodies in the field of intellectual property has been studied. Based on the analysis, practical proposals are given to improve the current legislation in the field of intellectual property.